Embodied affectivity: on moving and being moved - Fuchs, Thomas; Koch, Sabine C. (Frontiers in Psychology, 2014)
There is a growing body of research indicating that bodily sensation and behavior strongly influences one's emotional reaction toward certain situations or objects. On this background, a framework model of embodied affectivity1 is suggested: we regard emotions as resulting from the circular interaction between affective qualities or affordances in the environment and the subject's bodily resonance, be it in the form of sensations, postures, expressive movements or movement tendencies. Motion and emotion are thus intrinsically connected: one is moved by movement (perception; impression; affection2) and moved to move (action; expression; e-motion). Through its resonance, the body functions as a medium of emotional perception: it colors or charges self-experience and the environment with affective valences while it remains itself in the background of one's own awareness. This model is then applied to emotional social understanding or interaffectivity which is regarded as an intertwinement of two cycles of embodied affectivity, thus continuously modifying each partner's affective affordances and bodily resonance. We conclude with considerations of how embodied affectivity is altered in psychopathology and can be addressed in psychotherapy of the embodied self.